Ville et fleuve en Asie du Sud - Harit Joshi, Anne Viguier (dir.) (Presses de l'Inalco, 2016)
South Asia which is home to two of the largest river basins in the world has a long history of urban settlements. Several holy towns, believed to be the dwelling places of divine forces have come up along the banks of its rivers as have capital cities and centres of trade. By a study of seven cities and the rivers that flow through them, from Sehwan Sharif on the plains of the Indus in Pakistan to Guwahati on the banks of the Brahmaputra in the state of Assam, from Varanasi and Delhi based r...